An approach for fatigue life prediction based on external heating. (15th August 2021) - Hajshirmohammadi, B.; Khonsari, M.M.
Highlights: An experimentally verified method for estimating fatigue life is presented External heating source can generate surface temperature profile that matches cyclically loaded specimen Energy consumption of external heat source can be used to estimate fatigue life Abstract: An approach is presented to predict fatigue life and energy dissipation based on the measurement of the electrical power consumption of an external heat source. In this method, the steady-state temperature profile of a specimen experiencing cyclic fatigue test is reproduced simply by externally heating the specimen with an electric coil with a DC source. The results show a direct relationship between the electric power consumption of heating coils and the fatigue plastic energy dissipation. This relationship is used as a tool to predict fatigue life. Graphical abstract: Image, graphical abstract